12 The use of simulation training to improve the fundamental skills of junior trainees in laparoscopic surgery. (17th November 2016) - Vusirikala, A; Saunders, A; Feely, NM; Salerno, G
Abstract : Background: The Framework for Technology Enhanced Learning (2011) makes it clear that trainees should learn skills in a simulation environment before undertaking them in supervised clinical practice. 1 The aim of this pilot was therefore to help trainees develop the basic technical skills (hand- eye coordination, dexterity and motor skills) required to perform laparoscopic surgery. Methodology: A laparoscopic skills course was set up for Foundation Programme doctors and core trainees (surgery and obstetrics and gynaecology). Senior general surgeons taught fundamental laparoscopic skills which included basic thread transfer, precision cutting, dice stacking, paper fold, paperclip untangle, suturing, intracorporeal knot tying and tube ligation using dry materials. Each session was attended by 6–9 trainees, with 2 trainees working in a pair at each laparoscopic simulation trainer. An audio-visual presentation was viewed at the start of the session. The task was then repeated multiple times by each trainee. A pre- and post-session feedback questionnaire was used to assess improvement in confidence on a 4 point scale (1: no confidence - 4: very confident). Potential impact: Only 8% of participants had any previous experience using laparoscopic surgical simulators. The mean baseline level of confidence across all skills was 1.1 (range 1–3). The mean post-session level of confidence was 2.45 (range 2–4), with a mean uplift in confidence of 1.3 points (range 1–3). Our course highlighted that laparoscopic surgical simulators are a valuable tool to increase exposure and confidence of junior trainees prior to undertaking laparoscopic surgery in a supervised clinical environment. Our aim is to further develop this course at a deanery level and incorporate simulation with wet materials in the future. Reference: Department of Health/Workforce. A Framework for Technology Enhanced Learning 2011. [Available: https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/215316/dh_131061.pdf]